The impact of green digital finance on energy resources and climate change mitigation in carbon neutrality: Case of 60 economies. (December 2022) - Yu, Huaying; Wei, Wei; Li, Jinhe; Li, Ying
Abstract: Renewable energy projects have difficulties accessing finance, and digital finance can help fill the green finance gap. This study uses panel data from 60 emerging and non-emerging economies collected between 2010 and 2020 by employing pooled mean group method to show how green digital finance affects climate change mitigation from a resource-constraint viewpoint. The findings demonstrate that advocating for digitally accessible green finance helps to develop green and renewable energy resources and reduce CO2 emissions. The study provides practical policy recommendations. Highlights: Digitally accessible finance helps reduce CO2 emissions in cities. CO2 in metropolitan areas benefits from a solid positive geographical spillover effect. Inclusive digital finance has a more profound impact on lowering CO2 emissions in highly industrialized, high-income cities.